Answer: {1, 2 , 3, 4, 5,6}
Step-by-step explanation:
A sample space is the set containing all possible outcomes for an event.
Given : Han rolls a standard number cube once.
The possible outcomes for rolling a standard number cube = 1, 2 , 3, 4, 5 ,6
So, the sample space would be = {1, 2 , 3, 4, 5,6}
Hence, the required sample space for Han = {1, 2 , 3, 4, 5,6}
n = 4
n = fraction 1 over 2
n = fraction 2 over 3
Answer: The correct option is
(C) n = fraction 1 over 2.
Step-by-step explanation: We are to find the simplified form of the fraction 4 over 5 n minus fraction 1 over 5 equals fraction 2 over 5 n.
From the given information, we can write the equation as follows:
Solving the above equation, we get
Thus, the required simplified form is
Option (C) is CORRECT.
Answer:
Allentown(x) got 8 feet of snow and Georgetown(y) got 3 feet of snow
Step-by-step explanation:
Allentown got 2 feet less than twice the amount of snow Georgetown got . Allentown got 3 feet more snow than Georgetown.
Allentown = x and Georgetown=y
To solve this we need to represent this information mathematically;
'Allentown got 2 feet less than twice the amount of snow Georgetown got' can be written mathematically as; x = 2y - 2
and
'Allentown got 3 feet more snow than Georgetown' can be mathematically written as x = y + 3
x= 2y - 2 ----------------------(1)
x = y + 3 --------------------------(2)
Subtract equation (2) from equation (1)
[ x-x=0 2y-y = y -2-3=-5]
0 = y - 5
To get the value of y, add 5 to both-side of the equation
0+ 5 = y-5+5
5=y
y=5
Substitute y=5 into equation (2)
x = y+3
x=5+3
x=8
Therefore Allentown(x) got 8 feet of snow and Georgetown(y) got 3 feet of snow
x=2y-2
x=y+3
Substitute the second equation into the first
y+3=2y-2
solve for y
y=5
plug into original
x=y+3=5+3=8 or x=2(5)-2=8
Allentown got 8 ft of snow, Georgetown got 5 ft of snow.
4 6/7 + 3 5/7=____
Answer:
8 4/7
Step-by-step explanation:
a, = -51+12(n-1)
O a = -39+12(n-1)
O a, = 12+(-39)(n-1)
O a = 12+(-51)(n-1)
Answer:
A. an = -51+12(n-1)
Step-by-step explanation:
edge quiz
The solution is, the explicit rule for the arithmetic sequence is
a n = -51 + ( n - 1 ) · 12 .
An arithmetic progression or arithmetic sequence is a sequence of numbers such that the difference between the consecutive terms is constant.
The nth term of AP : a_n = a + (n – 1) × d
here, we have,
given that,
a 2 = -39
a 2 = a 1 + 12
- 39 = a 1 + 12
a 1 = - 39 - 12
a 1 = - 51 ( first term )
The common difference is : d = 12
The explicit rule for the arithmetic sequence:
a n = a1 + ( n - 1 ) d
a n = -51 + ( n - 1 ) · 12
Hence, The solution is, the explicit rule for the arithmetic sequence is
a n = -51 + ( n - 1 ) · 12 .
To lean more on Arithmetic progression click:
#SPJ7
Answer: it's congruent to
Step-by-step explanation: